STUDI TENTANG TRADISI MANDI BALIMAU KASAI MASYARAKAT MELAYU PADA ERA MODERNISASI DI DESA PULAU BAYUR KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Epi Andriani; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract:This research is motivated by the implementation of the balimaukasai bathing tradition which has been handed down by the ancestors for a long time as preparation for entering the holy month of Ramadan. The balimau bath tradition includes bathing procedures and balimaukasai bathing equipment. So the formulation of the problem in this research is how is the implementation of the balimaukasai bath tradition in the Malay community in the Modernization Era in DesaPulauBayur, KecamatanCerenti,Kabupaten Kuantan singingi?. The purpose of this study was to find out how the implementation of the balimaukasai bath tradition in the Malay community in the modernization era in Desa Pulau Bayur, Kecamatan Cerenti,Kabupaten Kuantan singingi. This study uses a quantitative descriptive method. The research subjects were 30 respondents, including: traditional leaders, balimau bathing activities, the community and youth. The data collection instruments used in this study were questionnaires, observations, interviews and documentation and literature studies. The data analysis technique in this research is by using the formula P = 100%. Based on the results of the study, it can be concluded that the implementation of the balimau kasai bathing tradition follows the procedures that have been passed down from the past including the procedures for carrying out bathing balimau and balimau bathing equipment for the Malay community who can it is known from the results of the responses of the respondents as a whole answered